Attosecond time delay in multiphoton ionization. Issue 7 (January 2020) - Yang, W; Liu, X; Song, X; Li, P; Chen, J
Synopsis: Here with a semiclassical picture we show that, after emerging in the continuum state, the photoelectron can be temporarily re-trapped by the atomic potential in a quasi-bound state, stays there for hundreds of at-toseconds before it gets free again, which is the origin of the remarkable time delay in above threshold ionization experiment. Our results build a bridge between the seemingly unrelated quantum EWS and classical Coulomb-induced time delays, and hold promise for intuitive interpreting fundamental electronic processes in photophysical and photochemical experiments.